ANALISIS WACANA KRITIS TERHADAP NASKAH PUBLIKASI PIDATO KENEGARAAN PRESIDEN JOKO WIDODO DALAM RANGKA HUT KE-70 PROKLAMASI KEMERDEKAAN REPUBLIK INDONESIA - Mahmuda Nur, Dermawati; Catur Budiyono, Sunu (Universitas PGRI Adi Buana Surabaya, 2019)
Using language into the published manuscript of state speech of President Joko Widodo tended to not transparent, but contained of much meaning of rhetoric. So that, criticaldiscourse analysis (CDA) was chosen as an instrument for questioning some interests, valuesor instructions which were hidden behind of the language. This research aimed to describe textstructure, social cognition, and social context about published manuscript of state speech ofPresident Joko Widodo for 70rd anniversary of The Republic of Indonesia. Researcher used aqualitative approach for discourse analysis within theory of Teun A. van Dijk. Result of thisresearch was text structure about this published manuscript speech which included of 3sections, which were: macrostructure, superstructure and microstructure. About themacrostructure, the research focus was about its topic. About the superstructure, the researchfocus was its schema or its plot. While the microstructure, the observational focus were itssemantic, syntactic, and stylistic aspects. About the social cognition of this manuscript, itincluded 3 schemas or models, which were: person schemas, role schemas, and event schemas.Meanwhile, about the social context of this published manuscript of President Joko Widodo’sstate speech, it included of practice of power and also access which controlled over thediscourse.